Sholat Dhuha Dalam Peningkatan Akhlak Di Madrasah Ibtidaiyah Mifttahul Ulumjatisari Kabupaten Probolinggo - Devy Habibi Muhammad; Lisun Ibnu Fajar (Mutiara: Multidiciplinary Scientifict Journal, 2023)
Islamic education includes moral teachings among its teaching. Although it is know that Indonesia is predominantly a muslim country. The values of Islamic education are expanted to be instilled and practiced in Indonesia with the help of strong moral education. A strong moral foundation will enable individuals to develop into upright human beings. The significant percentage of children who do not respect their parents and teachers shows how poor the character and values of society are. teaching students to perfom the dhuha prayer is one way to address this issue. The purpose of this research is to develop dhuha prayer exercises to help students develop their character and morals. Fourth to sixth grade students at MI Miftahul ulum jatisari participated in this research. This study is classified as a field study because it is based on actual fieldwork conducted in the real world. The type of research beaing discussed is descriptive-qualitative. Data will be examined and explained based on the research objectives with the help of this research. The school principal and teachers participated as informats in this research at MI Miftahul ulum jatisari as will as students. The hebit of perfoming the dhuha prayer can improve students’ morals. The implementation of the dhuha prayer trains students to behave well towards parents, teachers,and others. By using the metodets’ faith at MI Miftahul ulum jatisari.